Evaluasi Pengaruh Sistem Informasi Manajemen (SIM) terhadap Kepuasan Pengguna di Instalasi Farmasi RS “X” di Cirebon dengan Model DeLone & McLean - - SUPRIYATIN; EDIATI SASMITO; ELINA ENDANG SULISTYOWATI (Jurnal Farmasi Indonesia, 2012)
Information systems and information technology has become an important part of businessand organizational success. Information systems have an important role is to support business processes and operations within the company to complete its tasks, and manage the data and obtain information, to improve the performance of companies or organization. To assess the performance of such systems based on user perceptions. The purpose of this study to determine the effect of SIM on user satisfaction on Pharmacy Installation of “X” Hospital in Cirebon. The research was conducted using questionnaires given to all users with SIM in Pharmacy Installation saturated sample method. Independent variables (system quality, information quality and service quality) with the dependent variable (user satisfaction) were analyzedby simple linier regression analysis and multiple linier regression analysis. The result showed that the type of quality system have a significant effect of 43,90%, 60,70% of quality information and service quality for 74,40 while the quality system, quality information and quality services jointly significant effect on user satisfaction by 75,20%.